Existence analysis of an optimal shape design problem with non coercive state equation. (April 2016) - Chakib, A.; Nachaoui, A.; Nachaoui, M.
Abstract: In this paper, a shape optimization problem, modelling a welding process, governed by a second order non coercive PDE is considered. The well posedness of the shape optimal design problem is showed using the degree of Leray–Schauder. Then the existence of an optimal solution is proved.